2018
DOI: 10.1097/md.0000000000012490
|View full text |Cite
|
Sign up to set email alerts
|

Oral health condition and occurrence of depression in the elderly

Abstract: Depression is a common disorder among the elderly; however, it is not a standard element of the ageing process. Depression can affect oral health as a result of neglecting oral hygiene procedures, cariogenic nutrition, avoidance of necessary dental care which leads to an increased risk of dental caries and periodontal disease.Assessment of the relationship of oral health parameters with depression.500 subjects aged ≥65 (mean 74.4 ± 7.4) were involved in the study. Dental condition (decay-missing-filled index [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
55
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 43 publications
6
55
1
3
Order By: Relevance
“…In general, individuals with depressive disorders can find activities of daily living, such as oral hygiene, challenging and may consume a cariogenic diet which in turn can lead to periodontal diseases and development of dental caries. 26 The National Center for Health Statistics reports 12.7% of the population has taken an antidepressant medication in the last month. 27 Our analysis adjusted for individuals taking antidepressant and/or antipsychotic medications, the rationale being that psychotherapeutic medications has been associated with a significantly greater risk for symptoms of xerostomia (dry mouth).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, individuals with depressive disorders can find activities of daily living, such as oral hygiene, challenging and may consume a cariogenic diet which in turn can lead to periodontal diseases and development of dental caries. 26 The National Center for Health Statistics reports 12.7% of the population has taken an antidepressant medication in the last month. 27 Our analysis adjusted for individuals taking antidepressant and/or antipsychotic medications, the rationale being that psychotherapeutic medications has been associated with a significantly greater risk for symptoms of xerostomia (dry mouth).…”
Section: Discussionmentioning
confidence: 99%
“…In general, individuals with depressive disorders can find activities of daily living, such as oral hygiene, challenging and may consume a cariogenic diet which in turn can lead to periodontal diseases and development of dental caries. 26 …”
Section: Discussionmentioning
confidence: 99%
“…High sugar consumption is also a risk factor for plaque accumulation and poor oral hygiene, which are risk factors for several oral and general health problems [ 12 ]. Depression leads to reductions in energy and self-esteem, which may lead to poor oral hygiene behaviors and health status [ 13 , 14 ]. Poor oral health is also a risk factor for depression [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequences to tooth loss are not only evident in the loss of oral functions and impaired quality of life, but also psychological disturbances are anticipated. A recent study found that among people aged 65 and over, the severity of depression increases with a higher number of missing teeth and the number of decayed teeth [20], an association that was detected previously between DM and depression [21].…”
Section: Discussionmentioning
confidence: 78%